Design of DRFM jamming simulator using virtual instrument - Wang Min; Jiang Yanwen; Fan Hongqi (Dianzi Jishu Yingyong, 2022)
In order to meet the technical verification and system testing requirements of radar countermeasures against digital radio frequency memory(DRFM) jamming, a modular, scalable, lightweight and portable vector signal transceiver combined with DRFM technology is designed. The simulator control part adopts a kind of flow controller to realize, and the effectiveness of the design is verified by the injection test of the radar and jamming simulator. This design can generate various types of radar jamming signals, including interrupted-sampling and repeater jamming according to the radar echo. It can realize multiple mission functions by replacing and expanding the board. It can be used in the construction of radar test environment to support the research and verification of radar anti-jamming technology.